Waspada Penyakit Degenaratif dengan Edukasi Pola Hidup Sehat - Antari, Ni Putu Udayana; Suena, Made Dharma Shantini (UNBI Mengabdi, 2024)
Untuk membantu masyarakat meningkatkan literasi kesehatan, terutama mengenai pencegahan penyakit degeneratif, program sosialisasi kesehatan dilakukan di TK Widya Kumara Batubulan. Program ini melibatkan orang tua, guru, dan anak-anak dengan metode ceramah untuk orang tua dan demonstrasi serta bermain peran untuk anak-anak. Kegiatan ini bertujuan untuk memberikan pemahaman tentang pentingnya pola hidup sehat dalam mencegah penyakit degeneratif. Evaluasi menggunakan kuesioner dengan skala Likert menunjukkan bahwa 87,8% peserta berencana untuk membagikan informasi yang diterima kepada orang lain, dan sebagian besar menganggap informasi yang diberikan sangat berguna. Hasil ini menunjukkan bahwa penyuluhan efektif dalam meningkatkan pengetahuan peserta mengenai kesehatan. Program ini diharapkan dapat menjadi model dalam upaya meningkatkan literasi kesehatan masyarakat dan mengurangi prevalensi penyakit degeneratif di masa depan.   To help children develop physical and psycho-social health, parents, teachers, and stake holders should support and guide children by demonstrating good practices. Thus, health workers can assist the community in improving their health literacy through health socialization. Socialization on healthy living to avoid degenerative diseases was held at Widya Kumara Batubulan Kindergarten and attended by parents, teachers, and children of Widya Kumara Kindergarten. Participants were given socialization on degenerative disease knowledge and introduction to the pharmacist profession. The activity used PowerPoint media with a lecture method to help deliver information to parents and demonstration and role-play methods to convey information to kindergarten children. The activity effectiveness assessment questionnaire showed that as many as (30.4%) of participants really understood (48.4%) understood and (21.2%) quite understood the material presented. Most participants considered the information received to be necessary. 87.8% stated that they would explain the information obtained to others. The socialization, delivered using demonstration and role-play methods, also showed the kindergarten children's enthusiasm for the health information presented.